2018
DOI: 10.1371/journal.pone.0195088
|View full text |Cite
|
Sign up to set email alerts
|

Estimated prevalence of undiagnosed atrial fibrillation in the United States

Abstract: IntroductionAs atrial fibrillation (AF) is often asymptomatic, it may remain undiagnosed until or even after development of complications, such as stroke. Consequently the observed prevalence of AF may underestimate total disease burden.MethodsTo estimate the prevalence of undiagnosed AF in the United States, we performed a retrospective cohort modeling study in working age (18–64) and elderly (≥65) people using commercial and Medicare administrative claims databases. We identified patients in years 2004–2010 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(112 citation statements)
references
References 17 publications
1
100
0
5
Order By: Relevance
“…Atrial fibrillation (AF) is a common cardiac rhythm disorder estimated to affect 5.3 million adults in the United States in 2009 1 . Most often it is a nonvalvular condition and it has long been recognized as a significant risk factor for disabling or fatal ischemic stroke and systemic embolism (SE) [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is a common cardiac rhythm disorder estimated to affect 5.3 million adults in the United States in 2009 1 . Most often it is a nonvalvular condition and it has long been recognized as a significant risk factor for disabling or fatal ischemic stroke and systemic embolism (SE) [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Additional to this data, it was shown that more than half of the population with undiagnosed AF was at moderate to high risk for stroke. The data of this study also showed that the targeted screening strategy may provide benefit especially in the high-risk subgroup of older than 65 years and with multiple CHADS2 risk factors [20]. In a meta-analysis that investigated patients presenting with a stroke or TIA, 7.7% of the patient were diagnosed with atrial fibrillation in the emergency department, with an additional 5.1% during the hospital stay [21].…”
Section: Discussionmentioning
confidence: 61%
“…A study showed that 700,000 people in the United States may have undiagnosed AF, with an estimated cost burden of 3.2 billion dollars [19,20]. It is well known that asymptomatic AF is associated with similar risk of all-cause death, cardiovascular death, and thromboembolism compared to symptomatic AF [21].…”
Section: Prevalence Of Subclinical Af In General Populationmentioning
confidence: 99%